Cách sử dụng hoán dụ và so sánh của N.V. Gogol trong tác phẩm “Những linh hồn chết” (trên cơ sở ngữ liệu “nhóm từ vựng chỉ trang phục”) / Nguyễn Bảo Khanh - Nguyễn, Bảo Khanh
Nikolai Vasilyevich Gogol is a well-known Russian novelist and playwright. The novel ‘Dead Souls’, one of his greatest literary works, chronicles the journeys of Chichikov, a middle-class young man in the Russian society of the time. The aim of Chichikov’s travels is to purchase dead serfs that have not been declared by their landowners in order to serve the landowners’ dishonest purposes. Through this novel, Gogol vividly describes the human life and the fraudulent society with serfdom in the nineteenth century. The novel also fosters higher values, which are to condemn the contemporary ruling authority as well as to describes the hope, the optimistic attitude and the crave for happiness of Russian people of the time. Dead Souls is a realist novel that successfully describes the social setting of Russia in the nineteenth century. Gogol is deemed be a master of using satirical language to ridicule the Russian society in his works. The realist writing style of Gogol often becomes lively by means of ironical exaggeration. This article analyses Gogol’s use of trope, particularly metonymy and simile, in ‘Dead Souls’, as a means of accentuating the characters’ personality traits.